Relationship between seminal plasma zinc and semen quality in a subfertile population - DMAB Dissanayake; P S Wijesinghe; W D Ratnasooriya; S Wimalasena (Wolters Kluwer Medknow Publications, 2010)
Rationale : Current knowledge on the relationship between seminal zinc levels and different parameters of human semen is inconsistent. Objectives : To assess the relationship between seminal plasma zinc and semen quality using two markers; zinc concentration (Zn-C) and total zinc per ejaculate (Zn-T). Design : The study was carried out as a cross-sectional study. Subjects and Methods : Semen parameters of 152 healthy men undergoing evaluation for subfertility were assessed. Seminal plasma zinc levels were determined using flame atomic absorption spectrometry. Zn-C, expressed as μg/mL, was multiplied by ejaculated volume to calculate Zn-T. Mann Whitney U test and Chi-square test were used to compare the zinc levels between different seminal groups when appropriate. Correlations were observed with Pearson's correlation of coefficient. Analysis was carried out using SPSS 10.0 for windows software. Results : Zn-C was low in 23 (15%) samples, while in 32 (21%) of the samples Zn-T was abnormal. The number of subnormal samples was high in the low-zinc groups compared with the normal-zinc groups, 15 vs. 8 (P > 0.05) for Zn-C and 28 vs. 4 (P < 0.001) for Zn-T. Zn-C was significantly high in the asthenozoospermics compared with the normal motile group; 138.11 μg/mL (83.92) vs. 110.69 11 μg/mL (54.59) (P < 0.05). Zn-T was significantly low in samples with hyperviscosity compared with samples with normal viscosity; 220.06 μg (144.09) vs. 336.34 μg (236.33) (P < 0.05). Conversely, Zn-T was high in samples with low viability compared with those with normal viability; 437.67 μg (283.88) vs. 305.15 μg (221.19) (P < 0.05). Weak correlations were found between Zn and some semen parameters. However, the correlation was negative between pH and Zn-C (r = -0.193, P < 0.05) as well as Zn-T (r = -0.280, P < 0.01). On the other hand, correlations were positive between Zn-T and sperm count (r = 0.211, P < 0.05). Conclusion : Count, motility, viability, pH and viscosity are affected by variations of seminal plasma zinc. Seminal plasma Zn-T is the better marker for assessing the relationship between zinc and semen quality.